Assessing seal carcasses potentially subjected to grey seal predation - van Neer, Abbo (Sci Rep, 2021)
In order to conduct an objective evaluation of potential ecological effects of grey seal predation on marine mammals, it is essential to establish a broad knowledge base helping in the thorough identification of such cases during post-mortem examination. The aim of this work is to report and discuss outcomes resulting from a retrospective evaluation of harbour (Phoca vitulina) and grey seal (Halichoerus grypus) stranding and necropsy data (n = 3274). In addition, the results are compared to a recent case of definite grey seal predation from Germany as well as reports from other countries. Carcasses potentially subjected to grey seal predation show severe lacerations with a circular pattern leaving a smooth, linear and cut-like wound margin. Large parts of skin and underlying tissue are detached from the body and loss of blubber is common. Occurrence frequencies of encountered lesions are presented and a list of parameters to be used for the assessment of similar cases as well as a complementary decision tree are suggested. With the proposed parameters, categories and tools, a baseline can be built in order to facilitate the standardised recognition of predation cases during post-mortem examinations of seals between groups working with populations across several geographic ranges.